Peran Guru Pendidikan Agama Islam Dalam Mencegah Kekerasan Peserta Didik di Madrasah - Firman Mansir (Intiqad: Jurnal Agama dan Pendidikan Islam, 2021)
This article explains the importance of religious education in providing values and preventing social violence inmadrasas,especiallyPAIteachers. The purpose of religious education inmadrasasis the same as the purpose of life that is owned by every human being, including Muslims. Education also aims to humanize humans, meaning that a student must be treated well and be able to respect their opinions even if they are wrong. However, as an educator, they must be able to guide them by using their intelligence to achieve the desired goals in the future. Therefore, the success or failure of thePAIlearning process is determined or influenced by environmental conditions, one of which is themadrasaenvironment. The role of PAIteachers in overcoming bullying behavior inMadrasasis divided into several stages. First, bullying behavior that involves physical means is an act of violence committed by the perpetrator of the bullying against. The victim by controlling the victim with the power possessed by the perpetrator. Second, bullying behavior that is verbal or non-physical means an act of violence committed by the perpetrator against the victim by using satire, threatening, slandering each other, bullying, insulting, and so on. This research is a type of research that uses a qualitative approach. Therefore, the presence of Islamic Religious Education Teachers is expected to change attitudes and behavior. Through learning provided by competent educators and must be sensitive to the situation because the teacher's role like as a facilitator and mediator for his students.